Analysis of the Effect of Profitability, Liquidity, Solvency, Company Size, and Audit Opinion on Audit Report Lag on Manufacturing Companies Listed in Indonesia Stock Exchange - Selfriatika Putri Kristiani S; Yeremia Siagian; Asry Pangaribuan; Tetty Tiurma Uli Sipahutar (Budapest International Research and Critics University, 2021)
The purpose of this study was to see if the variables of profitability, liquidity, solvency, company size, and audit opinion could be tested. From 2015-2019, manufakturing companies listed on the Indonesia Stock Exchange were used in this study. 167 companies were studied over 5 years, yielding 395 observation samples. The official website www.idx.co.id is used to collect data for this study. This study uses Multiple Linier Regresion with the SPSS type 22. According to findings of this Study, liquidity, and audit opinion have a significant impact on audit report lag, whereas profitability, solvency, and company size have no impact on audit report lag.